Pendampingan dan Analisis Kelayakan Usaha Kerupuk Ikan â€œAbizarâ€ di Desa Pangkahkulon, Ujung Pangkah -Gresik - Fuad, Mochamad Arif Zainul (International Journal of Community Service Learning, 2021)
This community service activity aims to provide assistance in the development and analysis of the feasibility of the fish cracker business in the Abizar home industry in Pangkahkulon Village, Ujung Pangkah-Gresik from various aspects. Assistance is carried out with several activities including the introduction and provision of production equipment assistance, marketing training, and financial management training. While the analysis of business feasibility is reviewed from several aspects, namely technical aspects of production, management, marketing, legality and financial aspects. The results of the analysis show that SMEs are generally feasible to run from the various aspects above. From the financial aspect which is the main indicator of business feasibility, there is a very large profit ratio, Net B/C ratio which reaches 5.05, Profitability of 40%, and R/C Ratio of 1.5 and a payback period of less than half a year, then this business well worth the effort and can be continued. Based on the business feasibility study, it can also be concluded that business assistance by providing production equipment assistance does not provide a new financial burden for entrepreneurs but instead increases business efficiency and profits. However, it still needs improvement, especially from the aspect of business legality because partner SMEs do not yet have legality at all.